The electrical axis of the heart in patients with atrial fibrillation before and after radiofrequency ablation - Rybchynskyi, S. V.; Brynza, M. S.; Volkov, D. Ye.; Yabluchanskyi, M. I. (Zaporozhye Medical Journal, 2018)
Aim – to study changes of the electrical axis of the heart in patients with atrial fibrillation before and after radiofrequency ablation with pulmonary veins isolation. Materials and methods. Data from the study of heart electrical axis (HEA) position in 40 patients (24 men and 16 women) with atrial fibrillation before and during acute postoperative period (3–7 days) after performed radiofrequency ablation with pulmonary vein isolation (RFA PVI) were presented. The values of vector α angle of HEA (αF QRS) and its projections to the frontal (αQRS max F), the sagittal (αQRS max Si) and the horizontal plane (αQRS max H) were determined for the averaged complex in 5 seconds. Patients were divided into 3 groups: the group 1 – normal position of HEA α = 30–70 (n = 10), the group 2 – deviations of HEA to the left α <30 (n = 23) and the group 3 – deviations of HEA to the right – α > 70 (n = 7). The analysis of the changes reliability after the operation was carried out using the Wilcoxon test. Results. It has been established that the initially bimodal distribution of resultant vector with maxima in the groups 1 and 2 changed to a unimodal asymmetric with a maximum value displacement to the group 1region. The changes in aF QRS max projections on a plane yielded little information. There was a change in the resultant aF QRS in all patients after RFA PVI and in one third (32.5 %) of the patients normalizing of the HEA position took place, and in 5 % – an increase in aF QRS with the transition to the group 3. Conclusions. A further study of aF QRS changes, a comparison of aF QRS and the atrial vector are required.